Contracting Models of the Phillips Curve : Empirical Estimates for Middle-Income Countries - Agenor, Pierre-Richard; Bayraktar, Nihal (World Bank, Washington, DC, 2014)
This paper provides empirical estimates of contracting models of the Phillips curve for four middle-income developing economies-Chile, the Republic of Korea, the Philippines, and Turkey. Following an analytical review, models with both one lead and one lag, and two lags and three leads, are then estimated using Generalized Method of Moments (GMM) techniques. The results indicate that for both Chile and Turkey past and future inflation are of about the same magnitude in affecting current inflation. In Korea past inflation has a larger impact on inflation, whereas in the Philippines it is future inflation that plays a larger role. Homogeneity restrictions are satisfied for Korea and Turkey, but not for Chile and the Philippines.